Mutagenic Effects of Ethylmethane Sulphonate on Eucalyptus camaldulensis Ã— E. tereticornis - Swarup, Renu; Kapoor, M. L. (Indian Forester, 1985)
Seeds of Eucalyptus hybrid FRI- 5 (E. camaldulensis x E. tereticornis) were treated with Ethylmethane sulphonote(EMS) (0.25,0.50,1.00%) at two mointure levels. Effect of EMS on the hybrid was assesed by measuring different parameter viz. Germination percentage, Germination value, Germination Energy index Radicle and hypocotyl length, cotyledon width and length; Green and dry weight, Chromosomal aberration at anaphase. Air dried seeds were observed to br highly sensitive in comparison to the pre-soaked seeds. In general reduction percentage increased with increasing doses .Stimulation was observed in a few parameters at lower concentration. Germination value and Radicle length were the most sensitive parameters. This study has revealed the possibility of advancing new technique and methods for inducing/ manipulating genetic changes in the tree.